Engineering Nanoporous Iron(III) Oxide into an Effective Water Oxidation Electrode - Haschke, Sandra; Wu, Yanlin; Bashouti, Muhammad; Christiansen, Silke; Bachmann, Julien (ChemCatChem, 2015)
The geometric effects of nanostructuring a pure Fe2O3 surface on its electrochemical water oxidation performance at neutral pH were systematically explored. Atomic layer deposition was used to coat the inner walls of cylindrical "anodic" nanopores ordered in parallel arrays with a homogeneous Fe2O3 layer. Annealing and electrochemical treatments generated a roughened surface, as demonstrated by X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy, the larger geometric area of which increases current densities. Combining these treatments with the "anodic" pore geometry delivered an effective increase in turnover by almost three orders of magnitude with respect to a smooth, planar Fe2O3 surface. However, the current density depended on the pore length in a non-monotonic manner. An optimal length was found that maximized turnover by equating the rate of transport in the electrolyte with that of charge transfer across the interface.
Keywords: atomic layer deposition; electrochemistry; iron oxide; mesoporous materials; oxygen evolution reaction